Impact of Sublethal Levels of Environmental Pollutants Found in Sewage Sludge on a Novel Caenorhabditis elegans Model Biosensor - McLaggan, Debbie; Amezaga, Maria R.; Petra, Eleni; Frost, Andrew; Duff, Elizabeth I.; Rhind, Stewart M.; Fowler, Paul A.; Glover, L. Anne; Lagido, Cristina (PLOS ONE, 2012)
A transgenic strain of the model nematode Caenorhabditis elegans in which bioluminescence reports on relative, whole-organism ATP levels was used to test an environmentally-relevant mixture of pollutants extracted from processed sewage sludge. Changes in bioluminescence, following exposure to sewage sludge extract, were used to assess relative ATP levels and overall metabolic health. Reproductive function and longevity were also monitored. A short (up to 8 h) sublethal exposure of L4 larval stage worms to sewage sludge extract had a concentration-dependent, detrimental effect on energy status, with bioluminescence decreasing to 50–60% of the solvent control (1% DMSO). Following longer exposure (22–24 h), the energy status of the nematodes showed recovery as assessed by bioluminescence. Continuous exposure to sewage sludge extract from the L4 stage resulted in a shorter median lifespan relative to that of solvent or medium control animals, but only in the presence of 400–600 µM 5-fluoro-2′-deoxyuridine (FUdR), which was incorporated to inhibit reproduction. This indicated that FUdR increased lifespan, and that the effect was counteracted by SSE. Exposure to sewage sludge extract from the L1 stage led to slower growth and a delayed onset of egg laying. When L1 exposed nematodes reached the reproductive stage, no effect on egg laying rate or egg number in the uterus was observed. DMSO itself (1%) had a significant inhibitory effect on growth and development of C. elegans exposed from the L1 stage and on reproduction when exposed from the L4 stage. Results demonstrate subtle adverse effects on C. elegans of a complex mixture of environmental pollutants that are present, individually, in very low concentrations and indicate that our biosensor of energy status is a novel, sensitive, rapid, quantitative, whole-organism test system which is suitable for high throughput risk assessment of complex pollutant mixtures.